Antimicrobial prescribing for hospital-acquired pneumonia. (2nd January 2020) - Felton, Tim; Wootton, Dan
Abstract : The impact of hospital-acquired pneumonia and the pressure to reduce unnecessary antibiotic prescribing has lead to the publication of prescribing guidelines from the National Institute for Health and Care Excellence. This editorial gives an overview of the guidelines and emphasises the need for more high-quality evidence to inform decision making in this group of patients.